Correction: Boron-doped few-layer graphene nanosheet gas sensor for enhanced ammonia sensing at room temperature. Issue 59 (30th September 2020) - Srivastava, Shubhda; Jain, Shubhendra K.; Gupta, Govind; Senguttuvan, T. D.; Gupta, Bipin Kumar
Abstract : Correction for 'Boron-doped few-layer graphene nanosheet gas sensor for enhanced ammonia sensing at room temperature' by Shubhda Srivastava et al., RSC Adv., 2020, 10, 1007–1014. DOI: ; 10.1039/C9RA08707A